GAMBARAN NYERI KEPALA PERI IKTAL PADA PENDERITA EPILEPSI YANG BEROBAT JALAN DI POLIKLINIK SARAF RS DR M DJAMIL PADANG - Meiti Frida* (Neurona Majalah Kedokteran Neuro Sains, 2009)
BACKGROUND EPILEPSY OFTEN COMES WITH CERTAIN DISEASE AS ITS COMORBID FACTOR HEADACHE AND EPILEPSY ARE COMMON FEATURES FOUND IN AMBULATORY PATIENT HEADACHE CAN OCCUR BEFORE DURING OR AFTER ICTAL PHASE THE AIM OF THIS STUDY IS TO CHARACTERISE THE PERIICTAL HEADACHE IN PATIENTS WITH EPILEPSY IN NEUROLOGY DEPARTMENT OF DR M DJAMIL HOSPITAL PADANG